Effectiveness of Delayed Central Clamping on Hematocrit Levels: A Systematic Literature Review: Efektifitas Penundaan Penjepitan Tapi Pusat Terhadap Kadar Hematokrit: Systematic Literatur Review - Deviyani, Gista Ayu; Rukmana, Siti; Widyaningsih, W; Qothrunnada, Salma; Chabibah, Nur (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Background: Delayed cord clamping (DCC) is a strategy for placental transfusion in newborns recommended by the obstetrics and gynecology community. Although not widely applied, umbilical cord milking (UCM) may result in faster transfusion when delayed cord clamping cannot be performed in neonates requiring resuscitation. Methods: Systematic review of various Meta-analysis and Randomized Control Trial journal articles. Data collection was taken from Pubmed databases and consisted of international journals that met the inclusion and exclusion criteria, 7 journals were obtained, published in 2020 - 2023. Results: There is a significant effect between the time delay of umbilical cord cutting on the hematocrit levels of infants. Conclusion: Delaying cord clamping has an effect on increasing hematocrit levels in newborns, and can be used as an alterative to prevent anemia in infants.